2019
DOI: 10.5194/isprs-annals-iv-2-w5-127-2019
|View full text |Cite
|
Sign up to set email alerts
|

Can Uav Lidar Derive Vertical Structure of Herbaceous Vegetation on Riverdike?

Abstract: <p><strong>Abstract.</strong> Herbaceous vegetation on riverdike is important to prevent soil erosion, which may lead to collapse of riverdikes and consequently severe flooding. To keep suitable vegetation condition and secure visibility of riverdike for inspection, managers need to know where thick and tall herbaceous vegetation grows on riverdikes in a cost effective manner. This paper aims to derive vertical structure of herbaceous vegetation on riverdike using UAV LiDAR. UAV LiDAR based i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…It is a non-destructive method to derive plant parameters in large area, compared to traditional destructive field measurement techniques (Catchpole and Wheeler, 1992). Using UAV LiDAR which is an active sensor, Miura et al (2019; estimated herbaceous vegetation height and its vertical structure on riverdike. With a combination of structure from motion (SfM) and multi-view stereo (MVS) technique, passively acquired UAV imagery can also generate 3D information.…”
Section: Figure 1 Miscanthus Sinensismentioning
confidence: 99%
“…It is a non-destructive method to derive plant parameters in large area, compared to traditional destructive field measurement techniques (Catchpole and Wheeler, 1992). Using UAV LiDAR which is an active sensor, Miura et al (2019; estimated herbaceous vegetation height and its vertical structure on riverdike. With a combination of structure from motion (SfM) and multi-view stereo (MVS) technique, passively acquired UAV imagery can also generate 3D information.…”
Section: Figure 1 Miscanthus Sinensismentioning
confidence: 99%
“…Several studies, which explored the potential of UAV LiDAR to estimate canopy height in grasslands, reported height underestimation ( Miura et al., 2019 ; Zhao et al., 2022 ). The underestimation would affect the estimation of grassland ecosystem functions related to canopy height and its heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Although grasslands may have a higher canopy density than forests, the gaps between grass individuals combined with high point cloud density allow UAV LiDAR to obtain reliable ground elevation information ( Getzin et al., 2021 ; Zhao et al., 2022 ). The height loss at canopy was proved to be the main cause which greatly reduced the accuracy of grassland height-related structural traits ( Miura et al., 2019 ). Zhao et al.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst unmanned aerial vehicle (UAV) technologies are becoming more popular for fine‐scale vegetation surveys over larger areas (e.g., Tay et al, 2018) many species still require ground‐survey by botanists to be accurately identified. Similarly, whilst LIDAR has considerable potential to measure general vegetation structure (Miura et al, 2019) identification to species level would still require more conventional methods such as point quadrats or pin frames. One obvious limitation of recording dominant or subdominant species is that it is less able to detect rare species or those with sparse cover abundance.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, whilst LIDAR has considerable potential to measure general vegetation structure (Miura et al, 2019) identification to species level would still require more conventional methods such as point quadrats or pin frames. One obvious limitation of recording dominant or subdominant species is that it is less able to detect rare species or those with sparse cover abundance.…”
Section: Introductionmentioning
confidence: 99%